Interpersonal Relationships in the Mode for „Others“ - Milkov, Luchiyan; Yankova, Miloslava (Research Papers, 2017)
The problem of the „Оther“ is universal, i. e., it shall be analyzed in all social sciences, but the content of philosophical and psychological and pedagogical concept „Other“ depends on the philosophical and life situation and formulation of the problem.Moral because – the responsibility will be to „Other“, the primary existence of the „I“, i. е., the starting point and not the product of society. And if there is betrayal, it becomes the transition from social to moral „I“.In this sense, postmodern ethics is that of Em. Levinas, who in the words of Fr. La Rueel is „thinking about“ the Other“, he „invented Another ethical“.
Keywords: Interpersonal relationships; For another; Morality; Personality structure